2004
DOI: 10.1007/s00441-003-0793-2
|View full text |Cite
|
Sign up to set email alerts
|

?1?1-Integrin is an essential signal for neurite outgrowth induced by thrombospondin type 1 repeats of SCO-spondin

Abstract: In the central and peripheral nervous systems a heterogeneous group of proteins constituting the thrombospondin superfamily provides a cue for axonal pathfinding. They either contain or are devoid of the tripeptide RGD, and the sequence(s) and mechanism(s) which trigger in vitro their neurite-promoting activity have remained unclear. In this study, we reconsider the problem of whether sequences present in the thrombospondin type 1 repeats (TSRs), and independent of the well-known RGD-binding site, may activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…In the present investigation, we found that axons of the PC that are in contact with aggregates of SCOspondin express integrin ␤1. The findings showing that blocking integrin ␤1 function impairs SCO-spondin effect on neurite outgrowth (Bamdad et al, 2004) support the idea that the colocalization we detected has functional implications.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present investigation, we found that axons of the PC that are in contact with aggregates of SCOspondin express integrin ␤1. The findings showing that blocking integrin ␤1 function impairs SCO-spondin effect on neurite outgrowth (Bamdad et al, 2004) support the idea that the colocalization we detected has functional implications.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, integrins interact with the TSR domain of several members of the TSR superfamily (Leu et al, 2003;Calzada et al, 2004;Short et al, 2005). Remarkably, activity-blocking antibodies against integrin ␤1 inhibited the ability of the TSR domains of SCO-spondin to induce neurite outgrowth in vitro (Bamdad et al, 2004). However, there are no in vivo studies revealing the presence of integrin ␤1 throughout SCO and PC development and its possible interaction with SCO-spondin.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombospondin itself enhances neurite outgrowth (O'Shea, et al, 1991) and the thrombospondin type-1 repeats of SCO-spondin bind to α 1 β 1 integrin to stimulate cell process extension in B104 cells, a neuronlike cell line (Bamdad, et al, 2004). Furthermore, other ECM proteins that contain thrombospondin-like motifs, such as heparin-binding growth-associated molecule (HB-GAM, also known as pleiotrophin) and midkine, increase neurite outgrowth in hippocampal neurons (Raulo, et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a ''molecular fasciculation'' originated by the contact between axons and SCO-spondin. The mechanism involved in this process is unknown, but it could be mediated by interaction with integrin b1, because axons of the PC express this receptor (Caprile et al, 2009) and activity-blocking antibodies against integrin b1 inhibit the ability of the TSR domains of SCO-spondin to induce neurite outgrowth in vitro (Bamdad et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This superfamily includes proteins expressed during neural development that have been involved in a variety of biological processes, including axonal pathfinding and neural crest cell migration (Adams and Tucker, 2000). (5) Peptides containing the TSR motifs of SCO-spondin interfere, by a mechanism mediated by integrin b1, with a variety of neuronal processes in vitro, including neuronal survival and neurite outgrowth (Gobron et al, 1996(Gobron et al, , 2000Monnerie et al, 1998;Meiniel, 2001;Meiniel et al, 2003;Bamdad et al, 2004). (6) SCO-spondin is basally secreted to the extracellular matrix, where it is in close contact with axons of the PC that express integrin b1 (Caprile et al, 2009).…”
Section: Introductionmentioning
confidence: 99%